Evolution of Student School Payment Administration from Excel to Laravel - Muhammad Subhana (bit-Tech, 2025)
This study aims to develop a web-based school payment administration system using the Laravel framework to address several challenges commonly found in manual payment processes, including duplicate financial records, delayed verification procedures, and limited access to payment information for parents. The research adopts a qualitative descriptive approach involving direct observation of existing administrative workflows, analysis of user needs, and expert validation conducted with administrative staff and school management. The system developed in this study integrates student profiles, parent information, payment transaction data, and staff audit trails into a centralized and structured platform.  Core features of the system include payment validation based on uploaded proof of transfer, automatic activity logging for administrative staff, generation of daily and monthly financial reports, and role-based access control to improve data security and accountability. Functional evaluation using BlackBox Testing demonstrates that all key features perform according to user expectations and operational needs. In addition, feedback from experts and school personnel indicates that the implemented system contributes to faster administrative processing, more organized financial documentation, and reduced risk of data inconsistencies that typically occur in manual systems. Overall, this study provides a model for an integrated and secure school payment administration system that enhances efficiency and accessibility for parents, administrative staff, and school management. The findings underscore the importance of web transformation in improving the reliability and transparency of school financial operations.